THE ROLE OF PARENTS IN TEACHED CHILDREN TO FAST RAMADHAN IN KUTOREJO VILLAGE, MOJOKERTO - Erwin Kusumastuti (Prodi Sosiologi Agama dan Asosiasi Sosiologi Agama Indonesia (ASAGI), 2022)
The month of Ramadhan is a month that is eagerly awaited by all Muslims. In this month we do the obligation that is to fast for one month. The role of parents is needed this month, where parents are obliged to educate and trained their children to fast during Ramadhan. This is also done by parents in Kutorejo Village, Mojokerto. This research is based because researchers are interested in the role of parents in carrying out their obligations to their children. The purpose of this study (1) is to find out the ways of parents in Kutorejo Village, Mojokerto Regency in training their children to fast. (2) knowing the difficulties of parents in Kutorejo, Mojokerto to train their children to fast. In this study the researchers used a qualitative method with a descriptive form. And the data collection technique was carried out by observing and interviewing the intended object, namely parents and children in Kutorejo, Mojokerto. From this study, it can be concluded (1) the method used by parents in Kutorejo, Mojokerto when their children were able to fasted without coercion and do their best will be given prizes. And the second way that parents do is with their habits being able to become a reflection for their children. (2) the difficullty of parents to train their children to fasted in Kutorejo, Mojokerto namely the difficulty of monitoring their children when playing with friends who were afraid that they will break their children’s fasting and secondly, the children were very difficult to wake up for sahur and the children want to hurry up, break fast before it’s time to break the fast. Keyword : the role of parents, fasting, difficulties